2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26895
|View full text |Cite
|
Sign up to set email alerts
|

Failure and Idea Evolution in an Elementary Engineering Workshop (Fundamental)

Abstract: Chelsea Andrews is a Ph.D. candidate at Tufts University in the STEM education program. She received a B.S. from Texas A&M University in ocean engineering and an S.M. from MIT in civil and environmental engineering. Her current research includes investigating how children engage in engineering design through in-depth case study analysis.c American Society for Engineering Education, 2016 Failure and Idea Evolution in an Elementary Engineering Workshop (Fundamental) AbstractIn the engineering education community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
3
7
1
Order By: Relevance
“…Those students whose designs initially failed and who subsequently engaged in failure analysis and improvement-akin to Crismond's four-part diagnostic troubleshooting process [9,10]-had a more robust understanding of reasons for design success or failure. Andrews work and our own also supports the idea that design testing processes need to be followed accurately and testing results be interpretable in order to support the failure analysis and improvement process [12,13].…”
Section: Resilient Productive Actionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Those students whose designs initially failed and who subsequently engaged in failure analysis and improvement-akin to Crismond's four-part diagnostic troubleshooting process [9,10]-had a more robust understanding of reasons for design success or failure. Andrews work and our own also supports the idea that design testing processes need to be followed accurately and testing results be interpretable in order to support the failure analysis and improvement process [12,13].…”
Section: Resilient Productive Actionsmentioning
confidence: 78%
“…• Denying that failure occurred by ignoring proper testing processes Andrews examined how upper elementary student thinking evolved within an engineering workshop. Andrews found that challenges that were too easy and thus, resulted in few design failures, did not push students to evolve in their thinking about the underlying reasons for design success [13]. Those students whose designs initially failed and who subsequently engaged in failure analysis and improvement-akin to Crismond's four-part diagnostic troubleshooting process [9,10]-had a more robust understanding of reasons for design success or failure.…”
Section: Resilient Productive Actionsmentioning
confidence: 99%
“…This may help reposition failure away from negative perceptions. Other studies on failure in engineering design have also shown the importance of facilitation and how frequent failure leads to a higher engagement with thoughtful design and engagement with ideas about phenomena (Andrews, 2016).…”
Section: Engineering Designmentioning
confidence: 99%
“…In addition, people may feel anxiety when pushed to iterate early and frequently (Dow et al, ). While some studies of iterative prototyping show middle school students engaging in many tries (Welch, ), they suggest that iterations can be unproductive without facilitators to help students reflect meaningfully on what went wrong and how to improve on the next try (Andrews, ). There are pragmatic barriers to iteration as well.…”
Section: Literature and Backgroundmentioning
confidence: 99%